PENDAPATAN PETANI PENGUSAHAAN KAYU JATI (Tectona grandis) DI DESA POVELUA KECAMATAN BANAWA TENGAH KABUPATEN DONGGALA - Tagfira, .; Umar, Syukur; Alam, Andi Sahri (Universitas Tadulako, 2018)
Teak is a plant that cannot be removed from Indonesia culture. Therefore, people in Povelua do some cultivation of teak wood since the income has very high economic value and it much demand by consumers. This study aimed to describe the farmersâ€™ income of teak wood cultivation. This study was conducted in December 2015 up to February 2016 in Povelua village of Centra Banawa at Donggala district. Data collection was administered through observation and interview by using Table Tally Sheet. Data were analyzed by field observation by way of intention (purposive sampling). Based on result study, the land area 1 ha with spacing 3 x 4 m, there is 833 tress. At the beginning of planting, the number of tress decreased during the harvest due to natural deathÂ and thinning activities, but the result still can be utilized. The Paper mil accepts the small teak wood. The condition of teak at the harvest time was 25 years old amounted 350 trees. The economic value of teak wood is counted based on the income obtained from selling the wood. A number of trees harvested as much 350 tress with the total volume 173,0925 m3/ha and the average diameter are 30 cm, average free branch height is 10 m with per cubic Rp. 1.200.000. Then, the total sales of 350 tress by the land area 1 ha Rp 207.711.000 and reduced by the wage of workers who cut down the trees is p. 5.000.000/ha, therefore the total prediction of selling the teak wood in 1 ha is Rp. 202.711.000.Keywords: Farmersâ€™ Income, Teak Wood, Povelua